The effectiveness of a cultural-based support group for Malay dementia caregivers in Kelantan, Malaysia: a pre-post intervention study - Zakaria, Rozanizam; Ab Razak, Asrenee (ASEAN Journal of Psychiatry, 2017)
Objective: The psychological impact of care giving responsibility for dementia patients is significant regardless of the cultural background. Most of the current advanced caregivers’ interventions, originating from developed western countries, do not necessarily apply to local settings. Hence, there is a need for an effective culturally competent psychological intervention for these caregivers. The aim of the study is to assess the effectiveness of the cultural-based support group for Malay caregivers of dementia patients in Kelantan towards their burden, anxiety and depression level, and quality of life. Methods: This was an experimental study, without control, investigating pre and post support group intervention effectiveness in reducing caregiver burden, anxiety and depression, and improving the quality of life. Sixteen caregivers completed the program, which involved seven fortnightly support group sessions with duration of 2 hours each, conducted over twelve weeks. Caregivers’ burden was assessed using Caregiver Strain Index (CSI) while their psychological well-being was objectively assessed using Hospital Anxiety and Depression Scale (HADS). WHO Quality of Life questionnaire (WHOQOL-BREF) was used to measure the quality of life. The validated Malay versions of the questionnaires were used. Results: There was a statistically significant reduction in the level of caregiver burden (p = or < 0.001). Measurement of both scores of anxiety and depression comparing pre and post intervention also showed improvement, but statistically were not significant. Assessment of caregivers’ quality of life showed statistically significant improvement in the domains of social, psychological and physical (all with the p-value <0.05). Discussion: Our cultural-based support group is an effective intervention to improve burden, psychological well-being and quality of life among local caregivers of dementia patients.